2003
DOI: 10.1177/0011128702239233
|View full text |Cite
|
Sign up to set email alerts
|

From the Jailhouse to Capitol Hill: Impacting Mental Health Court Legislation and Defining What Constitutes a Mental Health Court

Abstract: This article examines congressional testimony preceding the passage of legislation authorizing federal funds for mental health courts and makes the case for the importance of anecdotal evidence in the process. The magnitude of persons with mental illness in the criminal justice system is considered, as well as factors that have led to the criminalization of this population. The concept of therapeutic jurisprudence is discussed, and commonalities in the emergence of mental health courts and methods of supervisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 10 publications
0
16
0
1
Order By: Relevance
“…Many who work in the criminal legal system are not equipped to deal with mental illness. Therefore, it is not surprising that the criminal legal system tends to exacerbate mental illness (Slate, 2003). Research has shown that integrated care is most effective in reducing SMI and SUD rather than treating only one condition (Drake, Mueser, Brunette, & McHugo, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Many who work in the criminal legal system are not equipped to deal with mental illness. Therefore, it is not surprising that the criminal legal system tends to exacerbate mental illness (Slate, 2003). Research has shown that integrated care is most effective in reducing SMI and SUD rather than treating only one condition (Drake, Mueser, Brunette, & McHugo, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have attempted to redress the conceptual confusion surrounding mental health diversion (Goldkamp & Irons-Guyn, 2000;Steadman et al, 2001;Slate, 2003). From this work the following four key elements are associated with programs that were perceived to be successful and that are certainly applicable to pre-arrest diversion.…”
Section: Discussionmentioning
confidence: 99%
“…Although research has consistently found that MHC participants have more positive criminal justice outcomes (for example, fewer arrests or jail days) compared with similar individuals not in MHCs (7)(8)(9)(10)(11), it is unclear what leads to these successful outcomes. One assumption is that MHCs reduce recidivism through provision of outpatient mental health services, such as medication management, individual and group therapy, and intensive case management (5,7,12). However, despite the importance placed on the assumed link between community treatment and recidivism, research on this relationship is rare (13,14).…”
mentioning
confidence: 99%